Kedudukan Hukum Pembebanan Hak Tanggungan Atas Pembagian Hak Bersama - Hidayati, Taufika; Erma, Zetria (Universitas Pahlawan Tuanku Tambusai, 2024)
This research examines the legal mechanism of encumbering Mortgage Rights on joint marital property, focusing on procedural and juridical implications. Employing a normative juridical research method, the study comprehensively analyzes legal dynamics related to property rights transfer within inheritance and credit guarantee contexts. The research aims to identify legal and procedural prerequisites for encumbering Mortgage Rights involving joint assets, considering the requirement of consent from all legal heirs. The study concentrates on registration mechanisms at the Land Office and their legal implications for creditor and debtor rights certainty. Research findings reveal the complexity of Mortgage Rights encumbrance, requiring multi-party coordination and consent. The findings emphasize the importance of formal documentation and systematic procedures to prevent potential future legal disputes, especially in asset execution scenarios where debtors fail to meet their obligations. This research provides significant contributions to understanding the legal framework governing asset transfer and rights encumbrance, offering a comprehensive perspective on the juridical complexities within inheritance and credit guarantee systems in Indonesia.